A PARADIGM SHIFT WELLBEING METHODOLOGY IN SOCIAL AND HUMANITIES RESEARCH - Suriadi, Jadi Suriadi (Journal of Critical Realism in Socio-Economics (JOCRISE), 2023)
This research delves into the intricate aspects of methodology, presenting a series of procedural steps utilized in empirical research titled "Wellbeing Methodology: A Comprehensive Approach to Evaluating Public Contentment Regarding Municipal Services in Bau Bau City, Southeast Sulawesi, 2023." Within this study, we employ the Wellbeing Methodology (WM), tailored to scrutinize public concerns and governmental policies, specifically concentrating on appraising public satisfaction with the services delivered by the municipal administration in Bau Bau City, Southeast Sulawesi, during the year 2023. WM offers a holistic framework that assesses diverse dimensions of public welfare, with a primary focus on the elements of Perception, Participation, and Acceptance (PPA). We have collected data, including respondent identification, PPA evaluation scores, and community input, which are presented in visual formats such as graphs and diagrams. This study aims to explore residents' satisfaction levels regarding various government services and assess the significance of the Perception, Participation, and Acceptance (PPA) variables in shaping overall societal well-being, referred to as the "Index of Public Well-being". It addresses crucial research inquiries, bridges existing research gaps, and also solicits community feedback in the form of suggestions, recommendations, and critiques to pinpoint areas ripe for improvement. The collected data will be leveraged to construct a Public Satisfaction Index, facilitating comparisons and discussions across diverse population segments. The data will undergo specific modes of analysis The data scores reveal a final score of 7.26 out of 9.0, indicating a highly positive interpretation. A total of 21 evaluation points were considered, all of which fall within the significant range. However, it's noteworthy that approximately 8% of respondents provided lower scores (ranging from 1 to 4), warranting further investigation. Additionally, this research endeavours to formulate a sustainability plan to ensure the continuous enhancement of community well-being. Through rigorous data analysis and widespread dissemination, this study contributes to a deeper understanding of public sentiment and the effectiveness of local government services, ultimately fostering improvements in governance and public welfare.